Operator training requirements and diagnostic accuracy of Fibroscan in routine clinical practice. Issue 1058 (7th August 2013) - Armstrong, M J; Corbett, C; Hodson, J; Marwah, N; Parker, R; Houlihan, D D; Rowe, I A; Hazlehurst, J M; Brown, R; Hübscher, S G; Mutimer, D
Abstract : Background: Fibroscan is a quick, non-invasive technique used to measure liver stiffness (kPa), which correlates with fibrosis. To achieve a valid liver stiffness evaluation (LSE) the operator must obtain all the following three criteria: (1) ≥10 successful liver stiffness measurements; (2) IQR/median ratio <0.30 and (3) ≥60% measurement success rate. Objectives: To assess the operator training requirements and the importance of adhering to the LSE validity criteria in routine clinical practice. Methods: We retrospectively analysed the LSE validity rates of 2311 Fibroscans performed (1 August 2008 to 31 July 2011) in our tertiary liver outpatients department at the University Hospital Birmingham, UK. The diagnostic accuracy of Fibroscan was assessed in 153 patients, by comparing LSE (valid and invalid) with the modified Ishak fibrosis stage on liver biopsy. Results: Learning curve analysis highlighted that the greatest improvement in validity of LSE rates occurs in the operator's first 10 Fibroscans, reaching 64.7% validity by the 50th Fibroscan. The correlation between LSE and the fibrosis stage on liver biopsy was superior in patients with a valid LSE (n=97) compared with those with an invalid LSE (n=56) (rs 0.577 vs 0.259; p=0.022). Area under receiving operating characteristics for significant fibrosis was greater when LSE was valid (0.83 vs 0.66; p=0.048). Using an LSE cut-off of 8 kPa, the negative predictive value of valid LSE was superior to invalid LSE for the detection of significant (84% vs 71%) and advanced fibrosis (100% vs 93%). Conclusions: Fibroscan requires minimal operator training (≥10 observed on patients), and when a valid LSE is obtained, it is an accurate tool for excluding advanced liver fibrosis. To ensure the diagnostic accuracy of Fibroscan it is essential that the recommended LSE validity criteria are adhered to in routine clinical practice.